Soluble bone marrow stroma factors improve the efficiency of retroviral transfer of the human multidrug resistance 1 gene to human mobilized peripheral blood progenitor cells - Schiedlmeier, Bernhard; Buß, Eike Christian; Veldwijk, Marlon Romano; Zeller, W. Jens; Frühauf, Stefan (Human gene therapy, 1999)
Hematopoietic stem cells (HSCs) are a potential target for the retrovirus-mediated transfer of chemotherapeutic drug resistance genes. For integration of the proviral DNA in the HSC genome cell division is required. In the bone marrow (BM) hematopoiesis occurs in the vicinity of stroma cells. Soluble stroma components were shown to play a permissive role for the proliferation of lineage-committed and primitive hematopoietic progenitors in conjunction with cytokines. We investigated the effect of stroma-conditioned medium (SCM) of the FBMD1 cell line on the gene transfer rate of the human multidrug resistance 1 (MDR1) gene contained in the retroviral SF-MDR vector into human mobilized peripheral blood progenitor cells (PBPCs) from tumor patients (n = 14) during transwell transduction in the presence of the recombinant fibronectin fragment CH-296.